Nemesis - Coulter, Catherine (New York : G. P. Putnam's Sons, 2015)
When Special Agent Lacey Sherlock foils a terrorist attack at JFK airport; another plot unfolds nearly simultaneously with a bomb at St. Patrick's Cathedral. The terrorist at JFK refuses to speak to anyone but Sherlock. Meanwhile, Savich--with the help of Agent Griffin Hammersmith--has his hands full trying to track an elusive murderer who looks like a Hollywood Dracula.
Keywords: United States. -- Federal Bureau of Investigation -- Fiction; Sherlock, Lacey (Fictitious character) -- Fiction; Savich, Dillon (Fictitious character) -- Fiction; Government investigators -- Fiction; Terrorism -- Prevention -- Fiction; Murder -- Investigation -- Fiction; Married people -- Fiction; Suspense fiction